Impact of Anthropogenic Activities on Vegetation Cover and Mammalian Herbivores in Afi Mountain Wildlife Sanctuary, Cross River State, Nigeria (2022)
Despite the popular perception of protected areas, forest resources are still subject to many forms of anthropogenic activities such as logging, hunting and burning. This necessitates the study on the impact of anthropogenic activities on vegetation cover and mammalian herbivores in Afi mountain wildlife sanctuary. Four communities around the study area namely; Ebok, kakukob, Esekwe and Olum were selected based on proximity to the sanctuary. Data on socio-economic characteristic and anthropogenic activities of the communities were determined using questionnaire. A total of sixty (60) copies of questionnaire, 15 each were distributed to the four communities. Dynamics in vegetation cover for 1985, 2000 and 2021 was determined using landsat imagery. Data were analyzed using descriptive statistics, Normalized Difference Vegetation Index. The result revealed that, males (65.0%) were the dominant respondents. The study respondents were in the age bracket between 41-50 years (51.6%) and majority (51.7%) can at least read and write. The result also indicates a drastic decrease in the forest cover as from 1985-2021, owning to increase in activities such as settlement, logging and farming within the sanctuary. Major threats to the vegetation cover and mammalian herbivores survival were farming, logging and illegal hunting. Conservation of the remaining forest resources should be given top priority.